Dorm-preneurship as Entrepreneurial Living and Learning: An Educational Design Ethnography - MacNeil, Ryan T.; Ochoa Briggs, Santana; Christie, Alisha E.; Sheehan, Connor (Entrepreneurship education and pedagogy, 2025)
Entrepreneurship residence halls/dorms have been appearing on more and more campuses, especially in the United States and Canada. However, there is a very thin knowledge base on which to construct and design these expensive campus facilities/programs. Sometimes called “dormcubators,” these facilities/programs are linked to both the university business incubation (UBI) and living-learning communities (LLC) movements. As a result, the design and delivery of these hybrid spaces/programs can be oriented toward achieving economic (i.e., starting companies), social (i.e., building communities), and/or educational (i.e., entrepreneurial learning) outcomes. Prior research on other kinds of post-secondary LLCs suggests that the intended outcomes are also likely accompanied by unintended negative consequences for students and faculty. To understand how various dorm-preneurship program designs have worked in practice, this paper applies an ‘educational design ethnography’ approach to four different residential entrepreneurship programs at the University of Waterloo, Canada. The key finding is that problems arise when dorm-preneurship programs lack any link to educational/curricular outcomes and focus only on economic objectives or social ones. Four design principles are developed to guide research and development of similar programs in other contexts.